Development of multifunctional nanocrystals for various applications - Chia, Stella Jia En (2016)
Nanosized metal nanostructures have gained very high popularity in the research field over recent years due to its ability to exhibit unique optical and electrical properties which could not be found in bulk materials. This report aimed to synthesise long gold (Au) nanorods and silver (Ag) nanowires which can be used in various applications. Gold nanorods were synthesized through seed-mediated growth process while silver nanowires were synthesized through polyol process method. Synthesized gold nanorods are expected to have a longitudinal surface plasmon resonance (LSPR) band above 800nm while synthesized silver nanowires are anticipated to achieve length greater than 50μm and diameter less than 100nm. The morphology and structure of synthesized nanostructures were analysed using a Transmission Electron Microscopy (TEM). Length of nanostructures were measured manually and the average length obtained were compiled in a plot and compared. The results obtained for the synthesis of nanostructures were not as consistent and desirable. Therefore, further study was conducted to study the effect of parameters that could affect the final morphology and structures of nanostructures. Parameters for gold nanorods include the amount of Hydrogen Tetrachloroaurate Trihydrate (HAuCl4.3H2O) and seed solution present in the growth solution. For silver nanowires, several parameters effect were studied including temperature, addition rate, concentration of stabilizer and amount of seed. The findings were supported and contradicted by theoretical prediction. Lastly, to improve the quality of nanostructures, three areas have been identified for further work.